Catalyst‐Free Three‐Component Tandem CDC Cyclization: Convenient Access to Isoindolinones from Aromatic Acid, Amides, and DMSO by a Pummerer‐Type Rearrangement. Issue 18 (21st March 2016) - Wang, Peng‐Min; Pu, Fan; Liu, Ke‐Yan; Li, Chao‐Jun; Liu, Zhong‐Wen; Shi, Xian‐Ying; Fan, Juan; Yang, Ming‐Yu; Wei, Jun‐Fa
Abstract: A catalyst‐free multicomponent CDC reaction is rarely reported, especially for the intermolecular tandem CDC cyclization, which represents an important strategy for constructing cyclic compounds. Herein, a three‐component tandem CDC cyclization by a Pummerer‐type rearrangement to afford biologically relevant isoindolinones from aromatic acids, amides, and DMSO, is described. This intermolecular tandem reaction undergoes a C(sp 2 )−H/C(sp 3 )−H cross‐dehydrogenative coupling, C−N bond formation, and intramolecular amidation. A notable feature of this novel protocol is avoiding a catalyst and additive (apart from oxidant). Abstract : Coupling without metal ! A three‐component tandem CDC cyclization by Pummerer‐type rearrangement to afford biologically relevant isoindolinones from acids, amides, and DMSO is described. This intermolecular tandem reaction undergoes a C(sp 2 )−H/C(sp 3 )−H cross‐dehydrogenative coupling, C−N bond formation, and intramolecular amidation (see scheme).